2010
DOI: 10.1007/s10689-010-9344-7
|View full text |Cite
|
Sign up to set email alerts
|

Successful oxytocin-assisted nipple aspiration in women at increased risk for breast cancer

Abstract: The high rate of interval malignancies urges for new screening methods for women at high risk for breast cancer. Nipple aspiration provides direct access to the breast tissue and its DNA, and therefore is a likely candidate, but clinical applications have been limited by the failure to obtain nipple aspiration fluid from most women. We performed oxytocin-assisted nipple aspiration in 90 women at increased risk for breast cancer based on family history or genetic test results (n = 63) and/or previous breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 10 publications
4
36
0
Order By: Relevance
“…In order to provide a suitable screen approach for breast cancer specific biomarkers, increased success in expression and collection will be required. Improved expression rates can be achieved with the aid of oxytocin nasal spray [18,40] as well as application of manual or mechanical pumps that are normally used for milk expression by mothers with preterm infants [41].…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide a suitable screen approach for breast cancer specific biomarkers, increased success in expression and collection will be required. Improved expression rates can be achieved with the aid of oxytocin nasal spray [18,40] as well as application of manual or mechanical pumps that are normally used for milk expression by mothers with preterm infants [41].…”
Section: Discussionmentioning
confidence: 99%
“…After this feasibility study, we started the prospective collection of nipple fluid in women at increased risk of breast cancer, our target population for introducing a potential new screening method. Preliminary results showed that NFA was also possible in this group of women [ 21 ]. In the present follow-up study, we show for the first time in a large group of high-risk women that repetitive NFA is a feasible and safe method.…”
Section: Discussionmentioning
confidence: 99%
“…Although low nipple volumes may hamper a multidisciplinary biomarker approach, we believe much of its limitations can be overcome due to the continuous development of increasingly sensitive techniques, and all-in-one DNA/RNA/protein isolation methods. Besides, we have already demonstrated that methylation analysis in nipple fluid samples from high risk women is feasible [ 21 ]. At this moment we are analysing the nipple fluid samples to investigate if the process of breast carcinogenesis can be predicted by the occurrence of methylation aberrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations